The Impact of Human Resource Development and Digital Culture on Employee Performance within the Tanjungpinang City Government - Saputra, Eka Kurnia; Moeins, Anoesyirwan; Marhalinda (Jurnal Ekonomi dan Bisnis Digital, 2024)
The purpose of this study is to investigate the evolution of human resources and digital culture on worker productivity. This study employs primary data and is descriptive quantitative in nature. The examples included in this research were 56 South Sulawesi Province Food Security Service employees. Use of SPSS version is required for the multiple regression analysis hypothesis test 26 software. The findings of this study demonstrate that employee performance is positively and significantly impacted by both digital culture and human resource development.